The impact of Otago exercise programme on the prevention of falls in older adult: A systematic review - Yang, Yi; Wang, Kun; Liu, Hengxu; Qu, Jiawei; Wang, Yan; Chen, Peijie; Zhang, TingRan; Luo, Jiong (Frontiers in Public Health, 2022)
Abstract: Objective: To improve the quality of life of the elderly in their later years, by increasing the physical activity participation of the elderly, the occurrence of falls accident scores in the elderly can be prevented. This paper comprehensively summarizes the origin, development, participation forms, and fitness effects of the Otago exercise program (OEP). Methods: Using PubMed, web of science, CNKI, dimensional spectrum, and other databases, search for research papers from 2005 to April 2021 by using keywords such as Otago project exercise; aged, Fall; Cognitive function, Balance ability, Lower limb strength, Fall efficiency, and so on. PEDro Scale was used to check the quality of the literatures. Results: A total of 34 papers were included after searching for kinds of literature related to the subject of this paper and after careful review by researchers. Conclusions: OEP is beneficial to improve the cognitive function of the elderly, enhance their lower limb muscle strength and dynamic and static balance ability, and then improve the gait stability and posture control ability of the elderly, which has significant positive benefits for the prevention of falls in the elderly. OEP is helpful to improve the falling efficiency of the elderly, help the elderly overcome the fear of falling, and form a positive emotion of "exercise improves exercise", to reduce the harm caused by sedentary behavior and the incidence of depression and improve their subjective well-being. Although OEP has significant positive effects on improving the health and physical fitness of the elderly, preventing falls, and restoring clinical function, the corresponding neural mechanism for preventing falls is not very clear. At the same time, how OEP can be combined with emerging technologies to maximize its benefits needs to be further discussed in the future.